Peningkatan Manajemen BUMDES dan Pengembangan Kewirausahaan Anggota Karang Taruna Berbasis Sumber Daya Lokal dan Ekonomi Kreatif di Desa Kutu Kulon Kecamatan Jetis Kabupaten Ponorogo - Setianto, Rahmat Heru; Handriana, Tanti; Arina, Nidya Ayu (Universitas Airlangga, 2020)
Village-Owned Enterprises (BUMDesa) and Karang Taruna Desa Kutukulon since the establishment of BUMDesa in 2016 have not been able to significantly contribute to the development of economy of the society. Based on the analysis, some fundamental problems are observed, namely: traditional business management, production skills, materials and means of production, and marketing reach. The management problem is related to the managers' lack of understanding of the principles of modern management in business. The problem of production skills is related to the ability and skill to produce quality products as well as meet market tastes. Material problems and business facilities are related to the unavailability of adequate business tools/facilities to be able to produce quality products at an efficient cost. Marketing problems include managers' lack of understanding of effective marketing strategies and techniques. Community service activities aim to overcome the problems in these various problems. This program provides training and assistance in relation to each problem identified, as well as the procurement of materials and production facilities to improve the quality and competitiveness of BUMDesa products. The output of this program is the implementation of modern management principles in the BUMDesa, increasing the quality and quantity of products, increasing marketing reach, increasing revenues of BUMDesa and the income of society. This community service program is expected to produce outcomes in the form of (1) publications in ISSN/Proceedings (published) journals; (2) publication in print/online/repository mass media; (3) videos of activities that were published in campus media; (4) the development of BUMDesa so that it can increase community empowerment